Implementation of Merdeka Belajar to Improve Creativity and History Learning Outcomes of Grade XI Social Science 2 Students at SMAN Ajibarang - Parsini (Mitreka Satata: Journal of Historical Studies and History Education, 2025)
This study was conducted with the aim of determining the extent to which the implementation of the Merdeka Belajar (Freedom to Learn) policy in history education can improve student learning outcomes and creativity at SMA Negeri Ajibarang. The research was carried out on 11th grade social science students (Class XI IPS 2) during the second semester of the 2022/2023 academic year, which took place from February to May 2023. The subject matter studied was Indonesia’s response to imperialism and colonialism. The method used in this study was classroom action research. In this classroom action research, the primary data source came from students, and secondary sources came from informants. Based on these techniques—documentation, observation, questionnaires, and tests—the instruments used included documents, pre-test and post-test items for Cycle I and Cycle II. This classroom action research used content validation. Observation results, test scores, and questionnaires were first analyzed by calculating totals and percentages before being interpreted in descriptive form. Data gathered during the research, from the initial condition through to Cycle II (final condition), showed improvement, although still slightly below the KKM. The average score increased from 57.83 in the initial condition, to 69.11 in Cycle I, and 75.67 in Cycle II. Meanwhile, creativity levels also increased—from 65.34% in the initial condition, to 71.69% in Cycle I, and further to 77.58% in Cycle II. Student creativity based on the "creative" and "very creative" categories increased from 13 students (36.11%) in the initial condition, to 25 students (69.44%) in Cycle I, and 27 students (75%) in Cycle II (final condition). Given the improvement in both learning outcomes and creativity in each cycle, it can be concluded that the implementation of Merdeka Belajar in history lessons can enhance student achievement and creativity.